Real civil precautionary measures in the Peruvian Criminal Procedural Code - Velásquez Oyola, María Rosario (2019)
This paper reflects on the real civil precautionary measures in the Peruvian Criminal Procedural Code that are included sparsely in our code and lack a systematic order, particularly if one considers that the rules to dictated them can be found in Plenary Agreement No. 7-2011/CJ-116, adopted by the Supreme Court Plenary Division. As a result of the foregoing, this research offers an overall view of the regulation of the real precautionary measures in the Civil Procedural Code and Criminal Procedural Code of Peru, to articulate them in both bodies of law, as well as in their enforcement.